Transient Receptor Potential Channel and Interleukin-17A Involvement in LTTL Gel Inhibition of Bone Cancer Pain in a Rat Model. (July 2015) - Wang, Juyong; Zhang, Ruixin; Dong, Changsheng; Jiao, Lijing; Xu, Ling; Liu, Jiyong; Wang, Zhengtao; Lao, Lixing
Cancer pain management is a challenge for which Chinese herbal medicine might be useful. To study the spinal mechanisms of the Chinese medicated gel Long-Teng-Tong-Luo (LTTL), a 7-herb compound, on bone cancer pain, a bone cancer pain model was made by inoculating the tibias of female rats with Walker 256 cells. LTTL gel or inert gel, 0.5 g/cm 2 /d, was applied to the skin of tumor-bearing tibias for 21 days beginning a day after the inoculation. Mechanical threshold and paw withdrawal latency to thermal stimulation was measured. Transient receptor potential (TRP) cation channels in lumbar dorsal root ganglia (DRG) were immunostained and counted, and lumbar spinal cord interleukin-17A (IL-17A) was measured with real-time polymerase chain reaction and enzyme-linked immunosorbent assay. TRP antagonists and interleukin (IL)-17A antibodies were intrathecally administered to determine their effects on bone cancer pain. The gel significantly ( P < .05) alleviated cancer-induced mechanical allodynia and thermal hyperalgesia and inhibited cancer-enhanced expression of IL-17A in spinal astrocytes and the TRP subfamily members V1, A1, and V4 in lumbar DRG. Intrathecal TRP antagonists at 10 µg significantly ( P < .05) attenuated mechanical allodynia, thermal hyperalgesia, and IL-17A expression, indicating that TRP channels facilitate spinal IL-17 expression and cancer pain. IL-17A antibodies inhibited cancer pain, suggesting that IL-17A promotes such pain. The data show that LTTL gel inhibits cancer pain, and this might be accounted for by the decrease in expression of DRG TRP channels and spinal astrocyte IL-17A.